(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
Acupuncture is a Chinese millennial technique that is being used within the Veterinary Medicine, which has two currents: traditional and transpositional, that is the used in Western medicine for its easy learning of the location of acupoints; this is based on channels (meridians) that run through the body and through these there is a flow of energy called Qi. Acupuncture is used for the treatment of different pathologies, focusing this article on those of the musculoskeletal and nervous system; en addition to helping with patient recovery, the use of acupuncture in horses improves their performance especially in those who are subjected to physical exertion. The stimulus generated by each puncture in a given acupoint, generates a beneficial effect for the patient, because they are areas with a high density of nerve endings, mast cells, lymph vessels, arterioles and venules, releasing post-stimulus endorphins; to generate the stimulation of acupoints there are several techniques, including the dry needle, electroacupuncture, moxibustion and implantation. The acupuncture can be used in horses in pathologies such as: lameness, claudications and low back pain; and in nervous conditions such as: radial nerve palsy, Wobbler syndrome and seizures; in addition improving the quality of life of both sick and healthy animals.